Characterization of Microbial Communities from the Rhizosphere of the Royal Palm (Roystonea oleracea) in a RAMSAR Wetland in Ecuador - Andrade, Jean Carlo; Santiago Mafla; Emily Avila; José Herándes (My University, 2024)
The interaction between the rhizosphere and the microbial communities that develop in this area is essential to understanding plant-microorganism processes such as nutrient availability or the development and suppression of plant diseases. Sequencing approaches have provided relevant insights into the microbiomes of plant rhizospheres such as the ecological interactions that are essential for the regulation of biogeochemical cycles inside wetlands. This research characterized some microbial communities present around an area close to the rhizosphere of the Roystonea oleracea palm. In this sense, ions present in four soil samples (M1, M2, M3 & M4) were quantified by spectrophotometry techniques to get an approximation of soil nutrients variation in this area. Later, the metabolic diversity of the bacterial communities cultivated from the samples was carried out using the BIOLOG EcoPlate™ kit. In addition, some isolated strains were analyzed through DGGE analysis of the 16 s rDNA gene amplified by PCR, founding that the most representative genera of the microorganisms obtained were Bacillus and Bovista. The results of a multidimensional scaling analysis of the banding pattern showed that M1 and M4 are 80% similar to each other. Finally, an antagonism test was performed between the microbial communities resulting in no antagonistic relationships observed.
Keywords: Microbial communities; RAMSAR; Rhizosphere; Wetland